Characteristic analysis of Omicron‐included SARS‐CoV‐2 variants of concern. Issue 2 (9th April 2022) - Yang, Hao; Liu, Penghui; Zhang, Yong; Du, Tingfu; Zhou, Yanan; Lu, Shuaiyao; Peng, Xiaozhong
Abstract: In view of the rapid development of the COVID‐19 pandemic and SARS‐CoV‐2 mutation, we characterized the emerging SARS‐CoV‐2 variants of concern (VOCs) by both bioinformatics methods and experiments. The representative genomic sequences of SARS‐CoV‐2 VOCs were first downloaded from NCBI, including the prototypic strain, Alpha (B.1.1.7) strain, Beta (B.1.351) strain, Delta (B.1.617.2), and Omicron (B1.1.529) strain. Bioinformatics analysis revealed that the D614G mutation led to formation of a protruding spike (S) in the tertiary structure of spike protein, which could be responsible for the enhanced binding to angiotensin‐converting enzyme 2 (ACE2) receptor. The epitope analysis further showed that the S protein antigenicity of the Omicron variant changed dramatically, which was possibly associated with its enhanced ability of immune escape. To verify the bioinformatics results, we performed experiments of pseudovirus infection and protein affinity assay. Notably, we found that the spike protein of Omicron variant showed the weakest infectivity and binding ability among all tested strains. Finally, we also proved this through virus infection experiments, and found that the cytotoxicity of Omicron seems to be not strong enough. The results in this study provide guidelines for prevention and control of COVID‐19. Abstract : In this study, we first predicted and compared the structure of the S protein and B‐cell epitopes of different SARS‐CoV‐2 variants. Then, the binding ability of different SARS‐CoV‐2 variant S proteins to angiotensin‐converting enzyme 2 (ACE2) cells and the affinity of RBD region to ACE2 were further compared through pseudovirus infection and intermolecular binding ability test. Finally, cell infection experiments were performed. The results unexpectedly showed that Omicron possesses lower ACE2 binding capacity, and lower replication capacity than Delta strain.